An ultrafiltration membrane with enhanced photocatalytic performance from grafted N–TiO2/graphene oxide. Issue 16 (3rd February 2017) - Chen, Wei; Ye, Ting; Xu, Hang; Chen, Taoyuan; Geng, Nannan; Gao, Xiaohong
Abstract : An ultrafiltration membrane with enhanced photocatalytic performance from grafted N–TiO2 /graphene oxide is prepared, characterized and tested. Abstract : An enhanced photocatalytic ultrafiltration membrane was prepared by grafting with N–TiO2 /graphene oxide. After N–TiO2 /graphene oxide particles and a polysulfone membrane had been prepared, the N–TiO2 /graphene oxide was distributed in deionized water, poured onto the membrane surface and grafted onto the membrane surface by using a pump filter. Scanning electron microscopy and atomic force microscopy were used to investigate the surface and morphological structure of the prepared membranes. Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy were used to analyze the elemental compositions and chemical bonds of the membranes. The hydrophilicity of the membrane surface was investigated by a sessile-drop method. The membrane water flux was tested in an ultrafiltration cup system. Methylene blue removal under darkness, ultraviolet light and sunlight were used to characterize the photocatalytic ability. The photocatalytic membrane exhibited an enhanced photocatalytic performance, especially in sunlight rather than in ultraviolet light. The synergistic effect of photocatalysis and filtration was tested; the photocatalytic membrane exhibited a better methylene-blue removal ability than a pure membrane as the methylene blue concentration in filtered water was lower. The recyclability of the photocatalytic membrane had a great improvement compared with the powder photocatalyst.